Organizational, technological, and pedagogical conditions for differentiated instruction of teaching English as a foreign language - Sarzhanova, G.; Otynshiyeva, M.; Tleuzhanova, G.; Assanova, D.; Sadvakassova, A. (International Journal of Education in Mathematics, Science, and Technology (IJEMST), 2023)
The aim of this study is to examine the relationships between differentiated instruction, pedagogical and technological competencies of students studying in the foreign language department. Differentiated instructional self-efficacy, pedagogical and technological competencies of students studying in foreign languages departments were examined in terms of grade level and perception of academic achievement within the scope of the comparative relational survey model. In the study, the relationships between differentiated instructional self-efficacy and pedagogical and technological competencies of students studying in foreign language departments were also examined on the basis of the relational survey model. The study was carried out on 234 students studying in foreign languages departments of different universities in Kazakhstan. Differentiated instructional self-efficacy, pedagogical and technological competence scales in the Likert-form were used to collect the research data. In the study, descriptive statistics F test and Regression analysis techniques were used in the analysis of the data. According to the research findings, the differentiated instruction self-efficacy, pedagogical and technological competencies of foreign language students were found to be moderate. Differentiated instructional self-efficacy, pedagogical and technological competencies of foreign language students differ according to their classroom and academic achievement perceptions. Finally, the pedagogical and technological competencies of foreign language students significantly affect their self-efficacy towards differentiated instruction.
Keywords: Pedagogical competence; Technological competence; Foreign language teaching; Kazakhstan; Differentiated instructional; self-efficacy